2017
DOI: 10.1111/bjd.15857
|View full text |Cite
|
Sign up to set email alerts
|

Clinical similarity of the biosimilar ABP 501 compared with adalimumab after single transition: long-term results from a randomized controlled, double-blind, 52-week, phase III trial in patients with moderate-to-severe plaque psoriasis

Abstract: ABP 501 and adalimumab have similar clinical efficacy, safety and immunogenicity profiles over 52 weeks, including after single transition, in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 20 publications
4
62
0
Order By: Relevance
“…The PASI 75 response rates observed in this study are higher than those seen in previous phase III adalimumab trials; however, they are in line with more recent studies, which may reflect the improved standard of care for patients with psoriasis. In AURIEL‐PsO, the proportion of patients with moderate disease was 70·0%, compared with previous studies ranging from 18·6% to 65·5% .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The PASI 75 response rates observed in this study are higher than those seen in previous phase III adalimumab trials; however, they are in line with more recent studies, which may reflect the improved standard of care for patients with psoriasis. In AURIEL‐PsO, the proportion of patients with moderate disease was 70·0%, compared with previous studies ranging from 18·6% to 65·5% .…”
Section: Discussionsupporting
confidence: 87%
“…In AURIEL‐PsO, the proportion of patients with moderate disease was 70·0%, compared with previous studies ranging from 18·6% to 65·5% . Previous studies with greater proportions of patients with moderate psoriasis also showed higher response rates . In addition, patients with psoriasis with a higher BMI have previously been shown to be less responsive to adalimumab or to discontinue earlier .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In open-label extensions of the PLANETAS study and the PLANETRA study, transitioning to the biosimilar infliximab-dyyb (CT-P13) after 54 weeks of treatment with reference infliximab did not result in a loss of efficacy or an increase in adverse events or immunogenicity (33,46). Comparable results have been observed in the open-label extensions of other studies (47,48), as well as in postmarketing observational studies (36,43,(49)(50)(51)(52)(53)(54)(55)(56).…”
Section: Extrapolation Of Indications Switching and Substitution Anmentioning
confidence: 85%
“…Evidence of equivalence between ABP 501 and reference adalimumab sourced from 3 RCTs: a phase 1, single-dose study in 501 healthy adults and 2 phase 3, randomized, double-blind studies, performed in patients with moderate to severe plaque psoriasis and moderate to severe RA, respectively. Both studies have demonstrated that ABP501 is similar to adalimumab in clinical efficacy, safety and immunogenicity [39][40][41][42].…”
Section: Adalimumab Biosimilarsmentioning
confidence: 99%